2015
DOI: 10.1021/acs.biomac.5b00823
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Anchor for Folate-Targeted Liposomal Delivery

Abstract: Specific folate receptors are abundantly overexpressed in chronically activated macrophages and in most cancer cells. Directed folate receptor targeting using liposomes is usually achieved using folate linked to a phospholipid or cholesterol anchor. This link is formed using a large spacer like polyethylene glycol. Here, we report an innovative strategy for targeted liposome delivery that uses a hydrophobic fragment of surfactant protein D linked to folate. Our proposed spacer is a small 4 amino acid residue l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…We previously demonstrated that the hydrophobic NPD inserts deeply into the lipid bilayer and anchors folate onto liposomal surface. 9 Also others have used hydrophobic peptides derived from bacteriophages and genetically fused them to targeting peptides to functionalize liposomes. 30,31 Now we show that NDP anchors onto liposomes without the need of harmful cross-linkers not only small ligands but also Fabs with the antigen-binding site well exposed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that the hydrophobic NPD inserts deeply into the lipid bilayer and anchors folate onto liposomal surface. 9 Also others have used hydrophobic peptides derived from bacteriophages and genetically fused them to targeting peptides to functionalize liposomes. 30,31 Now we show that NDP anchors onto liposomes without the need of harmful cross-linkers not only small ligands but also Fabs with the antigen-binding site well exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, NDP was successfully used to anchor folate into the lipid bilayer of the liposomes without affecting liposomal integrity. 9 Further, bioinformatic analysis of the NDP-heavy chain constructs revealed that NDP is extended away from the Fab variable and constant domains ( Supplementary Figure 2), indicating that the Fab fragments should be efficiently inserted into the liposomal membrane via the C-terminal hydrophobic peptide, with the N-terminal antigen-binding sites well exposed. Indeed, introducing NDP into the Fab sequences had no detrimental effect onto the Fab folding ( Figure 1, A and B) or their functionality (Figure 2, A right, 2, B right).…”
Section: Generation Of Fab Antibody Fragments With the Hydrophobic Pementioning
confidence: 99%
See 3 more Smart Citations